Composite diaphragm and preparation method and application thereof
By using inorganic hydrophilic cross-linked materials and polymer resins in the electrolysis water separator to form a cross-linked structure, the problems of low mechanical strength and poor hydrophilicity of traditional separators are solved, high toughness and low surface resistance are achieved, and the hydrogen production process is reduced. energy consumption in.
Patent Information
- Application Number
- CN202410467130.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-18
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-04-18
AI Technical Summary
Traditional electrolytic water diaphragms have low mechanical strength and are prone to cracking, resulting in a decrease in airtightness, increasing the risk of hydrogen leakage, and affecting the service life of the diaphragm. At the same time, organic toughening agents improve mechanical properties but affecting the hydrophilicity of the diaphragm and increasing energy consumption.
Inorganic hydrophilic cross-linked materials are used as toughening agents, which form a cross-linked structure with polymer resin through electrostatic, hydrogen bonding and other bonding interactions, thereby improving the mechanical strength and hydrophilicity of the separator and reducing surface resistance.
Improve the toughness of the separator, avoid cracking, reduce surface resistance, improve OH- ion conduction efficiency, and reduce energy consumption in the process of electrolyzing water to produce hydrogen.
Smart Images

Figure CN118374835B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water electrolysis, and in particular to a composite diaphragm and a preparation method and application thereof. Background Art
[0002] Hydrogen is an important energy source. Hydrogen combustion produces water and does not produce carbon greenhouse gases that have an impact on the environment. It is very environmentally friendly, which means that hydrogen will play an increasingly important role in future industrial production and social life. Among them, alkaline water electrolysis is one of the important sources of hydrogen production. Alkaline water electrolysis has high energy utilization, high hydrogen purity, and no pollution in the entire electrolysis process, so it has been studied more and more widely.
[0003] The alkaline water electrolysis device is provided with a diaphragm, which is used to separate the hydrogen and oxygen generated by electrolysis and to convert hydroxide ions (OH - ) from the cathode to the anode, etc. However, in traditional technologies, the diaphragm has low mechanical strength and is prone to cracking, which results in decreased diaphragm air tightness, increased hydrogen concentration in oxygen, increased risk of hydrogen leakage during the alkaline water electrolysis hydrogen production process, and reduced diaphragm life.
[0004] Traditional technologies use organic toughening agents to improve the mechanical properties of resin materials. The organic toughening agent can be polyoxymethylene (POM), polyvinyl chloride (PVC), polyethylene terephthalate (PET) or polyethylene terephthalate-1,4-cyclohexanedimethanol (PETG). Although the organic toughening agent can improve the mechanical properties of the resin material, it will affect the hydrophilicity of the water electrolysis diaphragm, thereby increasing the surface resistance of the diaphragm, and further increasing the energy consumption in the process of water electrolysis to produce hydrogen. Summary of the invention
[0005] Based on this, an embodiment of the present application provides a composite diaphragm with good toughness and low surface resistance, and a preparation method and application thereof.
[0006] In a first aspect, the present application provides a composite diaphragm, the composite diaphragm comprising a support layer and a slurry layer disposed on a surface of the support layer;
[0007] The slurry layer comprises a polymer resin, and a toughening agent and a hydrophilic agent dispersed in the polymer resin. The toughening agent comprises an inorganic hydrophilic cross-linking material, and the inorganic hydrophilic cross-linking material is cross-linked with the polymer resin.
[0008] In some embodiments, the inorganic hydrophilic cross-linked material includes at least one of a fibrous inorganic hydrophilic cross-linked material and a particulate inorganic hydrophilic cross-linked material.
[0009] In some embodiments, the fibrous inorganic hydrophilic cross-linked material has a length of 50 μm to 100 μm and a diameter of 1 μm to 5 μm.
[0010] In some embodiments, the fibrous inorganic hydrophilic cross-linked material includes at least one of lanthanum hydroxide whiskers, zinc oxide whiskers, and glass fibers.
[0011] In some embodiments, the average diameter of the particulate inorganic hydrophilic cross-linked material is 50 nm to 150 nm.
[0012] In some embodiments, the particulate inorganic hydrophilic cross-linked material includes at least one of silica and modified silica.
[0013] In some embodiments, the polymer resin includes at least one of polysulfone, polyethersulfone, polyarylsulfone, and polyphenylene sulfide.
[0014] In some embodiments, the hydrophilic agent includes at least one of zirconium oxide, magnesium oxide, aluminum oxide, titanium oxide, zirconium hydroxide, magnesium hydroxide, and barium sulfate.
[0015] In some embodiments, the composite membrane has a thickness of 0.35 mm to 0.75 mm.
[0016] In some embodiments, the slurry layer has a thickness of 0.20 mm to 0.50 mm.
[0017] In some embodiments, the thickness of the support layer is 0.10 mm to 0.30 mm.
[0018] In a second aspect, the present application provides a method for preparing the composite diaphragm as described in the first aspect, the preparation method comprising:
[0019] preparing a composite slurry comprising the polymer resin, the inorganic hydrophilic cross-linking material and the hydrophilic agent;
[0020] The composite slurry is used to form the slurry layer on the support layer.
[0021] In some embodiments, the mass proportion of the polymer resin in the composite slurry is 10% to 20%.
[0022] In some embodiments, the mass proportion of the inorganic hydrophilic cross-linking material in the composite slurry is 30% to 60%.
[0023] In some embodiments, the mass proportion of the hydrophilic agent in the composite slurry is 10% to 40%.
[0024] In some embodiments, the composite slurry further includes a porogen and an organic solvent.
[0025] Optionally, the mass proportion of the porogen in the composite slurry is 1% to 10%.
[0026] Optionally, the mass proportion of the organic solvent in the composite slurry is 1% to 5%.
[0027] Optionally, the porogen includes at least one of polyvinyl pyrrolidone, glycerol and polyacrylonitrile.
[0028] Optionally, the organic solvent includes at least one of N-methylpyrrolidone, dimethyl sulfoxide, dimethylacetamide and dimethylformamide.
[0029] In a third aspect, the present application provides an electrolysis device, comprising the composite diaphragm as described in the first aspect.
[0030] Compared with the traditional technology, this application has at least the following beneficial effects:
[0031] The present application adopts an inorganic hydrophilic cross-linking material as a toughening agent, which can not only form a cross-linking structure with the polymer resin through electrostatic, hydrogen bonding and other bonding effects, but also absorb the fracture energy when the diaphragm is subjected to external forces, thereby preventing the expansion of microcracks, thereby improving the toughness of the diaphragm and preventing the diaphragm from cracking; and because the toughening agent is hydrophilic, it can cooperate with the hydrophilic agent to improve the overall hydrophilicity of the diaphragm, thereby accelerating the OH - Ions are conducted in the diaphragm, reducing the surface resistance of the diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a schematic diagram of the cross-linking structure in the composite membrane provided in Example 1 of the present application.
[0033] Figure 2 Schematic diagram of the surface resistance testing device; wherein, 1-base; 2-lower electrode assembly; 3-upper electrode assembly; 4-support column; 5-connecting plate; 6-weight. DETAILED DESCRIPTION
[0034] Below in conjunction with the embodiments and examples, the present application is further described in detail. These embodiments and examples are only used to illustrate the present application and are not used to limit the scope of the present application. The purpose of providing these embodiments and examples is to make the understanding of the disclosure of the present application more thorough and comprehensive. It should also be understood that the present application can be implemented in many different forms, and is not limited to the embodiments and examples described herein. Those skilled in the art can make various changes or modifications without violating the connotation of the present application, and the equivalent form obtained also falls within the protection scope of the present application. In addition, in the description below, a large number of specific details are given in order to provide a more comprehensive understanding of the present application. It should be understood that the present application can be implemented without one or more of these details.
[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0036] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.
[0037] In this application, the terms "first", "second", etc. in "the first aspect", "the second aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0038] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0039] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to an integer in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical range disclosed in the present application should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows for a broad range of quantitative intervals such as percentage intervals, ratio intervals, and ratio intervals.
[0040] All documents mentioned in this application are cited as references in this application, just as each document is cited as reference separately. Unless they conflict with the invention purpose and / or technical solution of this application, the cited documents involved in this application are cited with all contents and all purposes. When the cited documents are involved in this application, the definitions of relevant technical features, terms, nouns, phrases, etc. in the cited documents are also cited. When the cited documents are involved in this application, the examples and preferred methods of the cited relevant technical features can also be incorporated into this application as references, but are limited to the implementation of this application. It should be understood that when the cited content conflicts with the description in this application, the present application shall prevail or be modified adaptively according to the description of this application.
[0041] In traditional technologies, organic toughening agents are used to improve the mechanical properties of resin materials. Organic toughening agents can be polyoxymethylene (POM), polyvinyl chloride (PVC), polyethylene terephthalate (PET) or polyethylene terephthalate-1,4-cyclohexanedimethanol (PETG). Although organic toughening agents can improve the mechanical properties of resin materials, they will affect the hydrophilicity of the electrolytic water diaphragm, thereby increasing the surface resistance of the diaphragm, and thus increasing energy consumption in the process of electrolytic water hydrogen production. However, the present application found that the use of inorganic hydrophilic cross-linking materials as toughening agents not only improves the mechanical strength of the diaphragm, improves the toughness of the diaphragm, but also improves the hydrophilicity of the diaphragm, thereby reducing the surface resistance of the diaphragm, and the voltage is lower and the energy consumption is lower in the process of electrolytic water hydrogen production.
[0042] In a first aspect, the present application provides a composite diaphragm, the composite diaphragm comprising a support layer and a slurry layer disposed on a surface of the support layer;
[0043] The slurry layer comprises a polymer resin, and a toughening agent and a hydrophilic agent dispersed in the polymer resin. The toughening agent comprises an inorganic hydrophilic cross-linking material, and the inorganic hydrophilic cross-linking material is cross-linked with the polymer resin.
[0044] The present application adopts an inorganic hydrophilic cross-linking material as a toughening agent, which can not only form a cross-linking structure with the polymer resin through electrostatic, hydrogen bonding and other bonding effects, but also absorb the fracture energy when the diaphragm is subjected to external forces, thereby preventing the expansion of microcracks, thereby improving the toughness of the diaphragm and preventing the diaphragm from cracking; and because the toughening agent is hydrophilic, it can cooperate with the hydrophilic agent to improve the overall hydrophilicity of the diaphragm, thereby accelerating the OH - Ions are conducted in the diaphragm, reducing the surface resistance of the diaphragm.
[0045] It should be noted that the inorganic hydrophilic cross-linking material in the present application refers to an inorganic hydrophilic material that can form a bonding cross-linking structure with a polymer resin.
[0046] In some embodiments, the inorganic hydrophilic cross-linked material includes at least one of a fibrous inorganic hydrophilic cross-linked material and a particulate inorganic hydrophilic cross-linked material.
[0047] The present application adopts fibrous or granular inorganic hydrophilic cross-linked materials, wherein the fibrous inorganic hydrophilic cross-linked materials are cross-linked with the polymer in a bridging manner in the resin matrix. When cracks appear, this bonding method will cause debonding, pull-out and other mechanisms, consume energy, slow down the growth of cracks, and have excellent toughening effects; the granular inorganic hydrophilic cross-linked materials have a large specific surface area and are well dispersed in the resin matrix, and have better hydrophilicity.
[0048] In some embodiments, the inorganic hydrophilic cross-linked material is modified, and a structure is grafted on the surface of the inorganic hydrophilic cross-linked material; optionally, the modification uses a material with ion-conducting properties, such as polymethyl acrylate, etc. The present application not only improves the cross-linking ability of the toughening agent by modifying the inorganic hydrophilic cross-linked material, but also selects a material with ion-conducting properties to improve the ion-conducting effect and reduce the surface resistance of the diaphragm.
[0049] In some embodiments, the length of the fibrous inorganic hydrophilic cross-linked material is 50 μm to 100 μm, for example, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm or 100 μm.
[0050] In some embodiments, the diameter of the fibrous inorganic hydrophilic cross-linked material is 1 μm to 5 μm, for example, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm or 5.0 μm.
[0051] In some embodiments, the aspect ratio of the fibrous inorganic hydrophilic cross-linked material is 10-100, for example, 10, 20, 30, 40, 50, 60, 70, 80, 90 or 100, preferably 10-40.
[0052] The present application controls the size of the fibrous inorganic hydrophilic cross-linked material, effectively ensuring that the fibrous inorganic hydrophilic cross-linked material has a toughening effect and a hydrophilic effect.
[0053] In some embodiments, the fibrous inorganic hydrophilic cross-linked material includes at least one of lanthanum hydroxide whiskers, zinc oxide whiskers, and glass fibers.
[0054] In some embodiments, the average diameter of the particulate inorganic hydrophilic cross-linked material is 50 nm to 150 nm, for example, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm or 150 nm.
[0055] In some embodiments, the particulate inorganic hydrophilic cross-linked material includes at least one of silicon dioxide and modified silicon dioxide. Optionally, the modified silicon dioxide may be polymethyl methacrylate (PMMA) modified silicon dioxide, wherein PMMA is grafted onto the surface of silicon dioxide.
[0056] In some embodiments, the polymer resin includes at least one of polysulfone, polyethersulfone, polyarylsulfone, and polyphenylene sulfide.
[0057] In some embodiments, the hydrophilic agent includes at least one of zirconium oxide, magnesium oxide, aluminum oxide, titanium oxide, zirconium hydroxide, magnesium hydroxide, and barium sulfate.
[0058] In some embodiments, the thickness of the composite membrane is 0.35 mm to 0.75 mm, for example, 0.35 mm, 0.40 mm, 0.45 mm, 0.50 mm, 0.55 mm, 0.60 mm, 0.65 mm, 0.70 mm or 0.75 mm.
[0059] In some embodiments, the thickness of the slurry layer is 0.20 mm to 0.50 mm, for example, it can be 0.20 mm, 0.22 mm, 0.24 mm, 0.26 mm, 0.28 mm, 0.30 mm, 0.32 mm, 0.34 mm, 0.36 mm, 0.38 mm, 0.40 mm, 0.42 mm, 0.44 mm, 0.46 mm, 0.48 mm or 0.50 mm.
[0060] In some embodiments, the thickness of the support layer is 0.10 mm to 0.30 mm, for example, 0.10 mm, 0.12 mm, 0.14 mm, 0.16 mm, 0.18 mm, 0.20 mm, 0.22 mm, 0.24 mm, 0.26 mm, 0.28 mm or 0.30 mm.
[0061] In some embodiments, the support layer includes one of a polyphenylene sulfide braided mesh, a polypropylene braided mesh, and a nylon braided mesh, preferably a polyphenylene sulfide braided mesh.
[0062] The second aspect of the present application provides a method for preparing the composite diaphragm according to the first aspect, the preparation method comprising:
[0063] preparing a composite slurry comprising the polymer resin, the inorganic hydrophilic cross-linking material and the hydrophilic agent;
[0064] The composite slurry is used to form the slurry layer on the support layer.
[0065] In some embodiments, the mass proportion of the polymer resin in the composite slurry is 10% to 20%, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.
[0066] In some embodiments, the mass proportion of the inorganic hydrophilic cross-linking material in the composite slurry is 30% to 60%, for example, it can be 30%, 33%, 36%, 39%, 42%, 45%, 48%, 51%, 54%, 57% or 60%.
[0067] The present application controls the mass proportion of the inorganic hydrophilic cross-linking material in the toughening agent in the composite slurry, effectively ensuring the high tensile strength and low surface resistance of the diaphragm, and avoiding problems such as low tensile strength caused by excessive inorganic material content.
[0068] In some embodiments, the mass proportion of the hydrophilic agent in the composite slurry is 10% to 40%, for example, it can be 10%, 13%, 16%, 19%, 22%, 25%, 28%, 31%, 34%, 37% or 40%.
[0069] In some embodiments, the composite slurry further includes a porogen and an organic solvent.
[0070] Optionally, the mass proportion of the porogen in the composite slurry is 1% to 10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.
[0071] Optionally, the mass proportion of the organic solvent in the composite slurry is 1% to 5%, for example, it may be 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5% or 5.0%.
[0072] In some embodiments, the porogen includes at least one of polyvinyl pyrrolidone, glycerol, and polyacrylonitrile.
[0073] In some embodiments, the organic solvent includes at least one of N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), dimethylacetamide (DMAc) and dimethylformamide (DMF). N-methylpyrrolidone is preferred. It is understood that the surface of the prepared diaphragm is more compact by selecting a solvent with a large difference in solubility parameter with water. For example, the difference in solubility parameter between NMP and H2O is 25, and the surface of the prepared diaphragm is compact, which can prevent H2 and O2 from mixing during the electrolysis process.
[0074] Exemplarily, a method for preparing the composite membrane is provided, comprising:
[0075] Mixing the hydrophilic agent and the organic solvent to form a premixed solution;
[0076] Adding polymer resin, toughening agent and porogen to the premixed liquid to form a composite slurry, the composite slurry comprises, by weight:
[0077] Polymer resin 10%~20%;
[0078] Toughening agent 1%~10%;
[0079] Hydrophilic agent 10%~40%;
[0080] Porogen 1%~5%; and,
[0081] Organic solvent 30%~60%;
[0082] The composite slurry is coated on a support layer, pre-evaporated, and then immersed in a water tank to obtain the composite diaphragm.
[0083] Among them, the stirring speed for forming the premix is 500r / min~3000r / min, for example, it can be 500r / min, 600r / min, 900r / min, 1200r / min, 1500r / min, 1800r / min, 2100r / min, 2400r / min, 2700r / min or 3000r / min.
[0084] Among them, the stirring speed for forming the composite slurry is 500r / min~3000r / min, for example, it can be 500r / min, 600r / min, 900r / min, 1200r / min, 1500r / min, 1800r / min, 2100r / min, 2400r / min, 2700r / min or 3000r / min.
[0085] Wherein, the pre-evaporation temperature is 20°C~80°C, for example, it can be 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C.
[0086] The pre-evaporation pressure may be normal pressure, for example, 100 kPa to 102 kPa.
[0087] The pre-evaporation time is 1 min to 10 min, for example, it can be 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min.
[0088] A third aspect of the present application provides an electrolysis device, which includes the composite diaphragm as described in the first aspect.
[0089] It should be noted that the electrolysis device in this application mainly refers to an alkaline electrolytic cell. In addition to the porous diaphragm, the alkaline electrolytic cell also includes electrodes, electrolyte and other necessary components. In this application, the materials and components of the electrodes and electrolyte are not limited.
[0090] It is understandable that the electrolysis device can be used to electrolyze any known components in the art, for example, electrolyze water to produce hydrogen, electrolyze chlorine and alkali, electrolyze carbon dioxide, or electrolyze sewage for treatment.
[0091] The embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. For experimental methods in the following examples where specific conditions are not specified, reference is given to the instructions given in the present invention first, and may also be based on the experimental manuals or conventional conditions in the field, or may be based on the conditions recommended by the manufacturer, or may refer to experimental methods known in the art. In the following specific examples, the measurement parameters of the raw material components may have slight deviations within the range of weighing accuracy unless otherwise specified. For temperature and time parameters, acceptable deviations caused by instrument test accuracy or operating accuracy are allowed. "Normal temperature" refers to 25°C; "normal pressure" refers to 100KPa or 101Kpa.
[0092] In the following examples and comparative examples, the support layer is a polyphenylene sulfide woven mesh with a thickness of 250 μm, purchased from Metas, with the brand name PPS 40-140-MTS.
[0093] Polysulfone resin was purchased from Solvay, USA, with the brand name Radel® R-5500.
[0094] PMMA modified silica was purchased from Inotech with the brand name SF-101.
[0095] Example 1
[0096] Add N-methylpyrrolidone and zirconium oxide powder into a vacuum mixer, and stir at a speed of 2000 r / min until they are evenly dispersed to obtain a premixed solution;
[0097] Add polysulfone resin (PSU), PMMA-modified silica and polyvinyl pyrrolidone to the premixed liquid, and stir at a speed of 2000 r / min until completely mixed and dissolved to obtain the composite slurry, wherein, in terms of mass percentage, the composite slurry includes:
[0098] Polysulfone resin 20%;
[0099] PMMA modified silica 1%;
[0100] Zirconia powder 28%;
[0101] Polyvinylpyrrolidone 1%; and,
[0102] N-methylpyrrolidone 50%;
[0103] The composite slurry was poured into the coating machine tank, evenly coated on the support layer, pre-evaporated at 25°C for 5 minutes, and then immersed in a water tank to obtain a composite diaphragm with a thickness of 0.5 mm. Figure 1 As shown, PMMA-modified silica is connected to polysulfone resin via hydrogen bonding and electrostatic cross-linking.
[0104] Example 2
[0105] A composite diaphragm was prepared according to the method of Example 1, except that, in terms of mass percentage, the composite slurry included:
[0106] Polysulfone resin 20%;
[0107] PMMA modified silica 5%;
[0108] Zirconia powder 24%;
[0109] Polyvinylpyrrolidone 1%; and,
[0110] N-Methylpyrrolidone 50%.
[0111] Example 3
[0112] A composite diaphragm was prepared according to the method of Example 2, except that N-methylpyrrolidone in the composite slurry was replaced by an equal mass of dimethylformamide.
[0113] Example 4
[0114] A composite diaphragm was prepared according to the method of Example 2, except that N-methylpyrrolidone in the composite slurry was replaced by an equal mass of dimethylacetamide.
[0115] Example 5
[0116] A composite diaphragm was prepared according to the method of Example 2, the only difference being that the PMMA-modified silica was replaced by glass fibers of equal mass, the length of the glass fibers being 80 μm and the diameter being 4 μm.
[0117] Example 6
[0118] A composite diaphragm was prepared according to the method of Example 1, except that, in terms of mass percentage, the composite slurry included:
[0119] Polyethersulfone resin 15%;
[0120] Lanthanum hydroxide whiskers 10%;
[0121] Magnesium oxide powder 10%;
[0122] Polyvinylpyrrolidone 5%; and,
[0123] N-Methylpyrrolidone 60%.
[0124] The length of the lanthanum hydroxide whisker is 50 μm and the diameter is 5 μm.
[0125] Example 7
[0126] A composite diaphragm was prepared according to the method of Example 1, except that, in terms of mass percentage, the composite slurry included:
[0127] Polyarylsulfone resin 10%;
[0128] Zinc oxide whisker 10%;
[0129] Titanium oxide powder 40%;
[0130] Polyvinylpyrrolidone 5%; and,
[0131] N-Methylpyrrolidone 35%.
[0132] The length of the zinc oxide whisker is 100 μm and the diameter is 1 μm.
[0133] Example 8
[0134] A composite diaphragm was prepared according to the method of Example 2, except that, in terms of mass percentage, the composite slurry included:
[0135] Polysulfone resin 20%;
[0136] PMMA modified silica 15%;
[0137] Zirconia powder 24%;
[0138] Polyvinylpyrrolidone 1%; and,
[0139] N-Methylpyrrolidone 40%.
[0140] Example 9
[0141] A composite diaphragm was prepared according to the method of Example 5, except that the diameter of the glass fiber was 16 μm and the aspect ratio was 5.
[0142] Comparative Example 1
[0143] A composite diaphragm was prepared according to the method of Example 1, except that, in terms of mass percentage, the composite slurry included:
[0144] Polysulfone resin 20%;
[0145] Zirconia powder 29%;
[0146] Polyvinylpyrrolidone 1%; and,
[0147] N-Methylpyrrolidone 50%.
[0148] Comparative Example 2
[0149] A composite diaphragm was prepared according to the method of Example 1, except that, in terms of mass percentage, the composite slurry included:
[0150] Polysulfone resin 20%;
[0151] PMMA modified silica 29%;
[0152] Polyvinylpyrrolidone 1%; and,
[0153] N-methylpyrrolidone 50%;
[0154] The composite diaphragm prepared above was subjected to performance testing, and the testing method included:
[0155] (1) Surface resistance test:
[0156] The test is carried out using a resistance test device composed of alkali corrosion resistant materials, such as Figure 2As shown, a support column 4 is provided on the base 1 of the resistance testing device, and a connecting plate 5 which can slide up and down along the support column 4 is provided on the support column 4. The upper electrode assembly 3 is provided on the lower surface of the connecting plate 5, and the lower electrode assembly 2 is provided on the upper surface of the base 1. The upper electrode assembly 3 and the lower electrode assembly 2 are arranged opposite to each other. The upper electrode assembly 3 and the lower electrode assembly 2 are both circles with a diameter of 3.57 cm and are made of nickel. In addition, a weight 6 is provided on the upper surface of the connecting plate 5 to apply pressure to the connecting plate 5.
[0157] Surface resistance test methods include:
[0158] S1. Cut the samples to be tested into specimens slightly larger than the size of the test plywood, a total of 5 pieces;
[0159] S2. Soak the sample in a potassium hydroxide solution at a temperature of (25±2)℃ for 4 hours;
[0160] S3, adjust the upper electrode assembly so that the upper electrode assembly contacts the lower electrode assembly, apply a pressure of 1kg to the upper electrode assembly, connect the upper electrode assembly and the lower electrode assembly to the positive and negative test clips of the AC low resistance meter respectively, and read the resistance value R1 when the phase is 0. The frequency range of the AC low resistance meter is 1-100kHz, and the voltage is 0.5V;
[0161] S4. Place the test diaphragm between the upper electrode assembly and the lower electrode assembly, measure the resistance value R2 of the sample, calculate the surface resistance R= (R2-R1) × S, and take the arithmetic average of 5 samples as the test result. Among them, R is the surface resistance of the diaphragm, Ω·cm 2 ; R1 is the resistance of the device body, Ω; R2 is the resistance of the device body and the diaphragm, Ω; S is the effective area of the electrode, cm 2 .
[0162] Tensile strength test: According to the provisions of GB / T 1040.3-2006, a type 2 specimen with a size of (150±0.5)×(15±0.1) mm was selected, the initial distance of the fixture was (100±5) mm, and the test rate was 100 mm / min.
[0163] The test results are shown in Table 1.
[0164] Table 1
[0165]
[0166] From the above table we can see that:
[0167] (1) Compared with Examples 3-4, it can be seen that the present application uses N-methylpyrrolidone as the organic solvent. The difference in solubility parameters between NMP and H2O is 25. The surface of the prepared diaphragm is dense, which can prevent the mixing of H2 and O2 during the electrolysis process. It not only has high tensile strength but also low surface resistance.
[0168] (2) Compared with Example 5, it can be seen that the fibrous inorganic hydrophilic cross-linked material selected in the present application has better tensile strength; the granular inorganic hydrophilic cross-linked material has better hydrophilicity, and thus the surface resistance of the diaphragm is low.
[0169] (3) Compared with Example 8, it can be seen that the present application controls the mass proportion of the inorganic hydrophilic cross-linking material in the toughening agent in the composite slurry, thereby having the advantages of low surface resistance and high tensile strength, and avoiding the occurrence of problems such as the increase in the content of inorganic hydrophilic cross-linking material and the decrease in the tensile strength of the diaphragm.
[0170] (4) Compared with Example 9, it can be seen that the present application controls the size of the fibrous inorganic hydrophilic cross-linked material, effectively ensuring that the fibrous inorganic hydrophilic cross-linked material has a toughening effect and a hydrophilic effect.
[0171] (5) Compared with Comparative Examples 1-2, it can be seen that the inorganic hydrophilic cross-linking material used in the present application as a toughening agent can not only form a cross-linking structure with the polymer resin through electrostatic, hydrogen bonding and other bonding effects, but also when the diaphragm is subjected to external forces, this cross-linking structure can absorb fracture energy and avoid the expansion of microcracks, thereby improving the toughness of the diaphragm and avoiding diaphragm cracking; and because the toughening agent is hydrophilic, it can cooperate with the hydrophilic agent to improve the overall hydrophilicity of the diaphragm, thereby accelerating the OH - Ions are conducted in the diaphragm, reducing the surface resistance of the diaphragm. The composite diaphragm of the present application improves the hydrophilicity of the diaphragm, and the surface resistance of the diaphragm is small, at 4000A / m 2 Under the current density, the voltage is smaller and the energy consumption is lower, which is suitable for industrial promotion and use.
[0172] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0173] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A composite diaphragm, characterized in that: The composite diaphragm comprises a support layer and a slurry layer arranged on the surface of the support layer; The slurry layer comprises a polymer resin, and a toughening agent and a hydrophilic agent dispersed in the polymer resin, the toughening agent comprises an inorganic hydrophilic cross-linking material, the inorganic hydrophilic cross-linking material is cross-linked with the polymer resin, and the inorganic hydrophilic cross-linking material comprises at least one of a fibrous inorganic hydrophilic cross-linking material and a granular inorganic hydrophilic cross-linking material; The fibrous inorganic hydrophilic cross-linking material comprises at least one of lanthanum hydroxide whiskers, zinc oxide whiskers and glass fibers, and the granular inorganic hydrophilic cross-linking material comprises at least one of silicon dioxide and modified silicon dioxide.
2. The composite diaphragm according to claim 1, characterized in that: The length of the fibrous inorganic hydrophilic cross-linked material is 50 μm to 100 μm, and the diameter is 1 μm to 5 μm.
3. The composite diaphragm according to claim 1, characterized in that: The average diameter of the particulate inorganic hydrophilic cross-linked material is 50nm to 150nm.
4. The composite diaphragm according to claim 1, characterized in that: The slurry layer satisfies at least one of the following conditions: (1) The polymer resin comprises at least one of polysulfone, polyethersulfone, polyarylsulfone and polyphenylene sulfide; (2) The hydrophilic agent includes at least one of zirconium oxide, magnesium oxide, aluminum oxide, titanium oxide, zirconium hydroxide, magnesium hydroxide and barium sulfate.
5. The composite diaphragm according to any one of claims 1 to 4, characterized in that: The composite diaphragm satisfies at least one of the following conditions: (1) The thickness of the composite diaphragm is 0.35 mm to 0.75 mm; (2) The thickness of the slurry layer is 0.20 mm to 0.50 mm; (3) The thickness of the support layer is 0.10 mm to 0.30 mm.
6. A method for preparing the composite diaphragm according to any one of claims 1 to 5, characterized in that: The preparation method comprises: preparing a composite slurry comprising the polymer resin, the inorganic hydrophilic cross-linking material and the hydrophilic agent; The composite slurry is used to form the slurry layer on the support layer.
7. The preparation method according to claim 6, characterized in that: The composite slurry satisfies at least one of the following conditions: (1) The mass proportion of the polymer resin in the composite slurry is 10% to 20%; (2) The mass proportion of the inorganic hydrophilic cross-linking material in the composite slurry is 30% to 60%; (3) The mass proportion of the hydrophilic agent in the composite slurry is 10% to 40%.
8. The preparation method according to claim 6 or 7, characterized in that: The composite slurry further comprises a porogen and an organic solvent.
9. The preparation method according to claim 8, characterized in that: The mass proportion of the porogen in the composite slurry is 1% to 10%.
10. The preparation method according to claim 8, characterized in that: The mass proportion of the organic solvent in the composite slurry is 1% to 5%.
11. The preparation method according to claim 8, characterized in that: The porogen includes at least one of polyvinyl pyrrolidone, glycerol and polyacrylonitrile.
12. The preparation method according to claim 8, characterized in that: The organic solvent includes at least one of N-methylpyrrolidone, dimethyl sulfoxide, dimethylacetamide and dimethylformamide.
13. An electrolysis device, characterized in that: The electrolysis device comprises the composite diaphragm according to any one of claims 1-5.
Citation Information
Patent Citations
Composite diaphragm for lithium ion batteries, production method thereof, and lithium ion battery
CN107437603A
Diaphragm for hydrogen production through water electrolysis, manufacturing method of diaphragm and water electrolysis device
CN116695175A
Composite diaphragm, preparation method thereof and battery
CN117080679A